Belajar dan Pembelajaran Sebagai Fondasi Pengembangan Potensi Peserta Didik - Susanti, Fitri; Usman, Syahruddin (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
Learning and instruction are two fundamental concepts in education that are closely related. Learning is defined as an internal process through which individuals acquire knowledge, skills, attitudes, and values through experience and interaction with the environment. Instruction, on the other hand, refers to a planned effort conducted by educators to create conditions that facilitate effective learning. This article aims to examine the concepts of learning and instruction and their relationship in improving educational quality. The method used is a literature review of relevant scientific sources. The results indicate that systematically designed, learner-centered instruction can promote meaningful learning processes.